Preparation and characterization of biocomposites based on chitosan and OPF nanocellulose - Muhammad Safwan Bin Mohaiyiddin (School of Materials Engineering, 2018)
This research sets out to examine the effect of nanocellulose reinforcement on the chemical and mechanical properties of chitosan biocomposites. There are three stages of studies were conducted for this research. There are extract of two different origins of nanocellulose which are from oil palm frond and commercial microcellulose; incorporation of nanocellulose extract into chitosan to form chitosan/nanocellulose biocomposites and chemical, mechanical and toxicity study of chitosan/nanocellulose biocomposites.